Surgical Management of Metastatic Breast Cancer: A Mini Review - Ueno, Takayuki (Frontiers in Oncology, 2022)
Breast cancer with distant metastases is a systemic disease. While systemic therapies are the main treatment strategy, locoregional therapy for metastatic breast cancer (MBC) is generally palliative only. However, recent progress in systemic and local therapies has improved the prognosis of patients with MBC and some may expect long-term survival. More vigorous local therapies for MBC may, therefore, be clinically justified in selected patients. A number of clinical trials and studies have investigated the clinical significance of surgical therapy for primary tumors and distant metastases in patients with MBC. Four prospective randomized trials and multiple retrospective studies have investigated the benefit of surgical resection of primary lesions in patients with MBC, with conflicting results. There have been a number of case-control studies examining the impact of surgical resection of distant metastases, but the benefit of this approach in terms of survival is controversial because selection bias is unavoidable in retrospective studies. The present review discusses the state of the literature relating to local management of the primary breast cancer through surgical resection and surgical management of distant metastatic lesions including pulmonary and liver metastases with future perspectives.